2021
DOI: 10.1109/jstars.2021.3065866
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Tropical Cyclone Wind Structure and Intensity From Spaceborne Radiometer and Synthetic Aperture Radar

Abstract: We present a relatively simple method to estimate tropical cyclone (TC) surface wind structure (34-, 50-and 64-kt wind radii) and intensity (maximum wind speed, MWS) from wind fields acquired from the L-band SMAP radiometer and C-band Sentinel-1A/B and RADARSAT-2 synthetic aperture radar (SAR) between 2015 and 2020. The radiometer and SAR-derived wind radii and MWS are systematically compared with the best-track estimates. The root-mean-square errors (RMSEs) of R34, R50 and R64 are 31.2, 21.8 and 17.0 n mi (1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…It has a strip width of 1000 km and can cover the global sea in 2-3 days [41,42]. The SMAP radiometer is derived from brightness temperature retrieval and has been proven to be an efficient microwave sensor for observing ocean surface winds [3,4,[43][44][45]. The SMAP radiometer can accurately estimate hurricane intensity (70 m/s) and wind radius, and the wavelength of the L-band is much larger than the radius of a raindrop, so high wind speed can be measured even under heavy rainfall conditions [43].…”
Section: L-band Smap Radiometers Datamentioning
confidence: 99%
See 2 more Smart Citations
“…It has a strip width of 1000 km and can cover the global sea in 2-3 days [41,42]. The SMAP radiometer is derived from brightness temperature retrieval and has been proven to be an efficient microwave sensor for observing ocean surface winds [3,4,[43][44][45]. The SMAP radiometer can accurately estimate hurricane intensity (70 m/s) and wind radius, and the wavelength of the L-band is much larger than the radius of a raindrop, so high wind speed can be measured even under heavy rainfall conditions [43].…”
Section: L-band Smap Radiometers Datamentioning
confidence: 99%
“…Tropical cyclones (TCs) produce strong winds, heavy rain, and high sea states in the sea, which pose a serious threat to marine navigation and the lives of coastal residents. The observation of TC wind speed is of major importance for TC monitoring and forecasting [1][2][3]. In recent years, the retrieval algorithms for the high wind speed of TCs have attracted extensive attention in the satellite oceanic remote sensing field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical comparisons between SMAP-derived TC surface wind speeds and SFMR along-track measurements, have shown that a standard deviation of wind speed of 3.11 m/s for wind speeds between 10 and 70 m/s (Meissner et al, 2017). Compared with the best-track reports, the RMSE of SMAP-derived maximum TC wind speed is 5.8 m/s, for the wind speeds in the range of 17∼80 m/s (Zhang et al, 2021). Moreover, a previous study has demonstrated that the combination of L-and C-band satellite radiometer observations has capability to provide valuable information about the TC surface wind structure (Reul et al, 2017).…”
mentioning
confidence: 96%
“…The RMSE of SAR-derived winds is about 5 m/s, for wind speeds up to 75 m/s (Mouche et al, 2019). Ocean surface wind fields from SARs and scatterometers have been widely used to analyze the characteristics of TC structure (Chavas & Emanuel, 2010;Zhang et al, 2020Zhang et al, , 2021.…”
mentioning
confidence: 99%